The effects of waste sorting in environmental microbiome, THP-1 cell viability and inflammatory responses - Viegas, Carla (2020)
Project EXPOsE - Project nº 23222 (02/SAICT/2016). Project "Waste Workers' Exposure to Bioburden through Filtering Respiratory Protective Devices” - Project IPL/2018/WasteFRPD_ESTeSL.